The effect of char particle size on the efficiency of solid-vapor separation in a fast pyrolysis cyclone system - Mohd Hafizuddin, Shahrin (2010)
In a fast pyrolysis process for the conversion of biomass into liquid and gas products, the role of the phase separation unit is critical to ensure the efficiency product recovery is high. For the pyrolysis system developed at Fakulti Kejuruteraan Kimia & Sumber Asli (FKKSA) Universiti Malaysia Pahang (UMP), the separation unit is designed with a cyclone separation system. Vapor product from the cyclone will enter condenser system to convert into liquid product. The collection efficiency of a cyclone separator depends on several factors including design parameters, such as dimensions of the cyclone separator, particle density, and operating temperature. The physical properties of fluid, namely the density and viscosity, and operating parameters such as the inlet velocity of the fluid into the cyclone and the outlet conditions also affect the cyclone efficiency. In this work, the effect of the particle size and temperature will be studied in order to get a higher efficiency of the separation process of cyclone system. Manual calculations of the collection efficiency were compared to the result of collection efficiency from CFD-Fluent simulation. It was found that the error is about 3.55%. Result shows that the increase of temperature vapor inside the cyclone system and particle size will decrease the separation of the cyclone system. As the temperature increase the air viscosity and density of the particle will decrease and it will lead to the lower separation efficiency of cyclone. This is same with particle size where separation efficiency decrease as the particle size increase due to the many of incomplete particle and most of the particle are stick to the cyclone wall and not being separated.